The Relationship between Cryptocurrency Prices and Share Prices of Technology Companies in Light of Covid-19 - Daho, Rachida Ben Ahmed (International Journal of Economics and Financial Issues, 2021)
BitCoin is a new digital currency that turned out to be quite interesting for the financial market. This digital currency has, in diverse manners, exhibited unique qualities in comparison with other financial assets, which certainly means that BitCoin investors may face more concerns and tradeoffs than those who choose more traditional investment opportunities. The present research paper primarily aims to show the importance of the BitCoin currency in the global markets and to highlight its relationship with the share prices of technology companies. It also tries to investigate and identify the most significant fluctuations that this sector witnessed in light of the Covid-19 pandemic, with a statistical analysis of ten technology companies during the period extending from 2015 to 2021. The findings of this study allowed concluding that a strong relationship exists between technology company share prices and BitCoin prices. It was also found that these companies greatly benefited from the Covid-19 pandemic and increased their profit rates, particularly information and communication technology companies. Keywords: BitCoin; Technology companies; Covid-19; Cryptocurrency; Share prices. JEL Classifications: F3, E4, G1, L1 DOI: https://doi.org/10.32479/ijefi.11718